Heroic Offerings: The Terracotta Plaques from the Spartan Sanctuary of Agamemnon and Kassandra - Gina Salapata (Les Carnets de l’ACoSt)
This monograph is a contribution to the study of religion in Sparta, one of Greece’s most powerful poleis, whose history is well known but whose archaeology has been much less satisfactorily explored. Through the comprehensive study of a distinctive class of terracotta votive offerings from a specific sanctuary, I shed light on both coroplastic art and regional religion; and by integrating archaeological, historical, literary, and epigraphic sources, I provide important insights into the heroic cults of Lakonia and contribute to an understanding of the political and social functions of local ritual practice.